Konsep Hedonisme dalam Al-Qur’an Perspektif Tafsir Al-Maraghi - Nissa, Sabilla Ainun; Faridah, Faridah; Murdianto, Murdianto (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This study looks at the idea of hedonism from Tafsir Al-Maraghi's point of view, as well as what it means and what its implications are in the Koran. The excess or overspending of the riches and blessings sent by God is the hedonism discussed in this study. Stated differently, hedonism is sometimes referred to as consumptiveness or wastefulness. Known for its comprehensive and topical analysis of the Koran and social life, Tafsir Al-Maraghi is a well-known tafsir that can offer significant insights on this particular theme. The objective of this study is to examine Tafsir Al-Maraghi's definition of hedonism, with particular attention on how pertinent verses from the Koran are interpreted. This study makes use of library research or research from libraries. This kind of library research uses written resources such as books, documents, and the like as its primary source of data. The Al-Maraghi commentary book by Ahmad Musthafa Al-Maraghi serves as the primary source for this study. The findings of the study demonstrate that hedonism is a reprehensible characteristic that stems from liver illness and negatively affects both social and personal life. The significant significance of the concept of hedonism is revealed by Al-Maraghi's interpretation, which links it to the ideas of monotheism, asceticism, and qona'ah. It also emphasizes how crucial it is to abstain from hedonism in order to preserve the world and the afterlife.